1963
DOI: 10.1071/ar9630460
|View full text |Cite
|
Sign up to set email alerts
|

Selection for fertility in Australian Merino sheep

Abstract: Phenotypic and genetic parameters for fertility in sheep, in terms of number of lambs born and number weaned, have been estimated in a flock of medium Peppin Merinos. Repeatability of fertility traits over all ages is low, but there is an age effect, the record at 3 years of age having a higher value than those at 2 or 4 years. The regression of subsequent performance on a difference of 1 lamb at the initial lambing was higher for the difference between 1 and 2 lambs than between 0 and 1 lamb, which indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

1973
1973
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…The comparable genetic correlation between NLB and WFS reported by Young et al (1963) was negative at -0.12. However, Young et al (1963) concluded that there is no indication of genetic and phenotypic antagonism between face cover and fertility in their study, possibly because of the absence of animals with heavily covered faces. Phenotypic and environmental correlations of ewe reproduction traits with subjective wool traits varied in sign and were mostly low in magnitude and negligible.…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…The comparable genetic correlation between NLB and WFS reported by Young et al (1963) was negative at -0.12. However, Young et al (1963) concluded that there is no indication of genetic and phenotypic antagonism between face cover and fertility in their study, possibly because of the absence of animals with heavily covered faces. Phenotypic and environmental correlations of ewe reproduction traits with subjective wool traits varied in sign and were mostly low in magnitude and negligible.…”
Section: Resultssupporting
confidence: 52%
“…In addition, sheep that have yellow wool are likely to wean more lambs. The genetic relationships between ewe reproduction traits over three lambing opportunities varied in sign (Table 6) and were significant between NLB3 and WFS (0.23 ± 0.11) and between TWW3 and FCS (-0.33 ± 0.16 Previous work on Australian Merino sheep (Young et al, 1963) reported both negative and positive relationships between NLB and WFS (in their study these authors term the trait 'face cover score', but their definition corresponds to WFS in the present study) measured at different ages. The comparable genetic correlation between NLB and WFS reported by Young et al (1963) was negative at -0.12.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many workers (Terrill & Stoehr 1942;Coop & Hayman 1962;Young et al 1963;Purser 1965;Lax & Brown 1968;Kennedy & Kennedy 1968;Edey 1970) have found that live weight and number of lambs weaned are positively associated. For example, an increase of 8 more lambs per 100 ewes joined per lQlb (4.5 kg) increase in body weight at 15-16 months of age was reported by Lax & Brown (1968), which is similar to the relationship with pre-mating weights found by Coop & Clark (1966).…”
Section: Discussionmentioning
confidence: 99%
“…Young et al 1963;Bradford 1985). However, selection for a single component of a composite trait does not always result in an overall improvement of a complex trait, such as reproduction or ewe productivity (Snowder 2002).…”
Section: Introductionmentioning
confidence: 99%